EXTERNAL STRATEGIC PLANNING ANALYSIS PRACTICES AND PERFORMANCE OF PERFORMANCE OF COFFEE FARMERS SOCIETIES IN BUNGOMA COUNTY, KENYA - Kipkania , Elijah Kipsoboi; Yatich, Henry (IJRDO - Journal of Business Management, 2023)
Cooperative organizations are established to collectively address economic challenges more effectively than individuals can on their own. However, achieving resolutions for farmers’ issues through cooperative societies is not automatic due to shared economic factors with other businesses, including international relations and regulatory limitations. Evaluating the equitable distribution of income among members becomes a gauge of their satisfaction with the benefits offered by newly formed cooperatives. The primary focus of this study was to assess the external strategic planning analysis practices on the cooperative society’s performance. The study was guided by stakeholder theory, growth theory, human capital theory, and dynamic capabilities theory. This study employed both descriptive and exploratory research approaches. Data collection involved a diverse group of participants, totalling 340 individuals. This group included 40 supervisors, 160 workers, and 140 manufacturing managers representing the cooperative society’s management. Questionnaires were administered to 75 plant managers, 21 supervisory managers, and 85 employees, resulting in a total of 181 respondents based on the Krejcie and Morgan (1970) sampling method. Descriptive data analysis was conducted using SPSS version 28, enabling the examination of both quantitative and qualitative information through coding. To assess the data both descriptively and inferentially, statistical techniques, including means, standard deviations, Pearson’s correlation, and regression analysis, were employed. There was a positive correlation between external strategic planning analysis practices and the cooperative society’s performance. Based on these insightful finding, the study recommended a more substantial integration of external strategic planning analysis practices in the running of cooperative societies. These implications held value for various stakeholders, including factory management, government entities, researchers, and academics. By providing actionable insights, this research facilitated informed decision-making, ultimately contributing to the enhanced performance of coffee farmers’ societies in Bungoma County, Kenya.